Diagnostic Accuracy of Serum Anti-Tissue Transglutaminase Antibody in Diagnosis of Pediatric Celiac Disease - Bela Bashir, Tufail Ahmed Soomro, Rizwana Qureshi, Muhammad Zaki, Bashir Ahmed Chandio, Mansoor Ahmed Bouk, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Celiac disease (CD) is an immune mediated enteropathy that is caused by intolerance to gluten storage protein of wheat bartey and rice. Early diagnosis of celiac disease is highly imperative to institute early intervention in order to prevent profound macronutrient deficiencies as well as long term complications. Diagnostic investigation for celiac disease, the matter of controversy, with endoscopic duodenal biopsy remaining the gold standard but invasive, costly, painful, needing expertise and carrying risks of endoscopy, while serologic tests although noninvasive, cheap, easily available but with disputed specificity and sensitivity. Objective: To find the accuracy and importance of anti-tissue transglutaminase IgA antibody in celiac disease diagnosis and determination in pediatric patients. Place and Duration of Study: Department of Pediatrics, GMMMC Hospital Sukkur from 1st June 2019 to 30th November 2019. Methodology: One hundred and fifty children were suspected celiac diseases were enrolled. Demographic data including age, gender was noted. Duodenal biopsy and upper GI endoscopy of all patients with positive anti-tTG was performed. At least 6 biopsy specimens were taken from first and second part of duodenum and duodenal bulb. Results: Mean age of the children was 8.72±1.92 years. Sensitivity, specificity, PPV and NPV of tTG-IgA in evaluating celiac disease was 86.9%, 84.8%, 88%, 83.6% and 86% respectively. Conclusion: Tissue transglutamianse (TTG) is an excellent screening test for celiac disease in high risk Paediatric population having diagnostic accuracy of 86%. Therefore, it can be safely recommended that patients having even fewer clinical features should be screened by TTG to detect celiac disease patients with minimal signs and symptoms. Keywords: Celiac disease, IgA anti-tissue transglutaminase, Gastrointestinal endoscopy